The Hungarian, Latvian, Lithuanian, Polish, Romanian, Russian, Slovak, and Spanish, adaptation of the Makarowski`s Aggression Questionnaire for martial arts athletes - Makarowski, R.; Görner, K.; Piotrowski, A.; Predoiu, R.; Predoiu, A.; Mitrache, G.; Malinauskas, R.; Vicente-Salar, N.; Vazne, Z.; Bochaver, K.; Cherepov, E.; Hamzah, I.; et al. (Archives of Budo, 2021)
Background and Study Aim: Studying aggression and aggressiveness among martial arts athletes allows for identifying aspects of the training process, important for the professional and personal development. Makarowski's Aggression Questionnaire has only been published in English in 2013. The aim of the current study is recommendation to researchers, coaches of various martial arts (combat sports) disciplines, physical education teachers, and sports psychologists with a measure of aggressiveness.